The Influence of Fashion Knowledge, Fashion Selection Factor, and Dress Etiquette on Dress Look - Fatwa Dewi Apriliani; Widihastuti; Rihab Wit Daryono; Daniel Jesayanto Jaya; Adilla Desy Rizbudiani (Jurnal Pendidikan dan Pengajaran, 2023)
Dharma Wanita members tend to pay less attention to ethics in dress and the use of uniform attributes according to regulations. This is caused by various professions, education, culture, and economy as well as a lack of knowledge about dressing. The purpose of this research is to analyze how the influence of fashion knowledge, clothing selection factors, and dress etiquette on dress appearance. The research was aimed at members of Dharma Wanita with a sample of 60 respondents taken by purposive sampling technique. A combination of factor analysis and regression analysis was used to analyze the data using second-order PLS-SEM analysis. Evaluation of the measurement model on convergent and discriminant validity as well as internal consistency reliability has met the requirements. The structural model evaluation shows a large influence contribution of 97.00%, and the research observation value is 60.10%. All hypotheses are accepted indicating that there is a positive and significant effect of all variables on dress appearance. Even though the category analysis is good, it is recommended for administrators provide rules for the use of work uniforms and good attributes to support work activities. Therefore, Dharma Wanita members can choose and repair clothes to make them more harmonious and beautiful to support their daily activities.